Analysis of Visual, Auditory, and Kinesthetic-Based Student Learning Styles in Science Subjects at SMPN 7 Muaro Jambi - Anisa Fitria; Ilham Falani; Riska Fitriani; Viola Amelia Syafitri (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
The study aims to study and analyze the learning style of students of the eighth grade at SMPN 7 Muaro Jambi, especially in the context of IPA learning. The focus of the study is to identify preferences of student learning style based on three main dimensions, namely visual, auditory, and kinesthetics. This research method uses a descriptive quantitative approach by involving eighth grade students as primary respondents. Research instruments in the form of questionnaires are designed to measure the preferences of students' learning styles according to visual, auditory, and kinesthetic characteristics. The total number of samples observed came from 8 classes with a total of 226 students of the 8th grade. Based on the data processing of the research it is known that the learning style of students on the subject of IPA Class VIII generally in SMPN 7 Muaro Jambi in 2023. A total of 45.13% or 102 respondents were visual in very high categories, as many as 32.74% or 74 auditory respondents with very high Categories and as much as 22.12% or 50 kinesthetic respondents in moderate categories. So from this study it can be concluded that the students of the eighth grade who follow the learning of IPA are more likely to the visual learning style with the highest percentage of 45.15%. The teacher who will teach in the class can adapt the model and learning media that corresponds to the learning style that the student has. The results of this study are expected to provide a better understanding of the learning style of students of the eighth grade at SMPN 7 Muaro Jambi, especially in IPA subjects.